Efektivitas pemberian jus tomat terhadaptekanan Darah pada penderita hipotensi - Lyra - Sriminda; Ari Pristiana Dewi; Ganis - Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research is to determinedthe effectivenessoftomato juiceonblood pressure of hypotensionpatients. The design of thisresearch is quasy experimentdesigned byNon-equivalent control groupweredivided intoexperiment groupandcontrol group. The research was conductedofhypotension patientinthe PuskesmasRumbai. The total sample are 50peoplewhowere takenby usingsimple randomtechniquesby noticing tothe inclusion criteria.Measuring instruments usedin the two groupsisthe observation sheet.The analysis usedwas univariateandbivariatealternativetestandWilcoxonMannWhitney.The results showeda significant differencebetween the meanbloodpressurebefore and afteradministration oftomatojuiceto the increase inbloodpressurep(0.000) <α (0.05).It’smeans thatin patent with hypotension effective to increase blood pressure. The results of this study recommend to apply tomato juice as an herbaltreatment to increase blood pressure. Keywords : hypotension, tomato juice